Review of Risk Management and Patient Safety in the Context of Hospital Quality Management: Literature Review - Asriani Asriani; Suci Dwi Yanti; Vergina Anggraini Abrar; Nurul Fajriah Istiqomah (LPPM ISTEK 'Aisyiyah Kendari, 2024)
Introduction: One of the elements of general welfare of national goals is the realization of optimal health. Therefore, quality health services will become one of the basic needs required by everyone. In improving quality and patient safety, there are risks that must be overcome to get the desired results, for this reason hospitals need to carry out risk management. Risk management is closely related to the implementation of patient safety and worker safety in hospitals and has an impact on achieving hospital quality, etc. Methods and materials: This research is a literature review based on sources from Google Scholar with the search keyword